2018
DOI: 10.1016/j.aim.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal free quantum group factors are strongly 1-bounded

Abstract: We prove that the orthogonal free quantum group factors L(FO N ) are strongly 1-bounded in the sense of Jung. In particular, they are not isomorphic to free group factors. This result is obtained by establishing a spectral regularity result for the edge reversing operator on the quantum Cayley tree associated to FO N , and combining this result with a recent free entropy dimension rank theorem of Jung and Shlyakhtenko.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…[22]. However, for O + N , even more is known: In [23] it was shown that in fact L ∞ (O + N ) is a strongly 1-bounded von Neumann algebra for all N ≥ 3. The notion of strong 1-boundedness was introduced by Jung in [30] and entails that δ 0 (X) ≤ 1 for any self-adjoint generating set X ⊂ L ∞ (O + N ).…”
Section: Remarks On Free Entropy Dimensionmentioning
confidence: 99%
“…[22]. However, for O + N , even more is known: In [23] it was shown that in fact L ∞ (O + N ) is a strongly 1-bounded von Neumann algebra for all N ≥ 3. The notion of strong 1-boundedness was introduced by Jung in [30] and entails that δ 0 (X) ≤ 1 for any self-adjoint generating set X ⊂ L ∞ (O + N ).…”
Section: Remarks On Free Entropy Dimensionmentioning
confidence: 99%
“…As has been known for over twenty years now, another source of operator algebras sharing many properties with these related to discrete groups is provided by the theory of compact (equivalently, discrete) quantum groups, as initiated by Woronowicz ([Wor98]), with the quantum theory encompassing its classical counterpart. Of particular interest is the class of universal quantum groups of Van Daele and Wang ([VDW96]), which leads to operator algebras behaving in many ways as these associated with the classical free groups ( [VV07]), but recently shown by Brannan and the last named author of this paper to be non-isomorphic to these at the von Neumann algebra level ( [BV18]).…”
Section: Introductionmentioning
confidence: 99%

Noncommutative Furstenberg boundary

Kalantar,
Kasprzak,
Skalski
et al. 2020
Preprint
Self Cite
“…Ever since their introduction these algebras have received considerable attention and in particular over the last few years significant structural results have been obtained for them. In particular, recently it was proved that free quantum groups can be distinguished from the free group factors [11]. Further, the following is known if we assume N ≥ 3 (the case N = 2 corresponds to the amenable SU q (2) case):…”
Section: Introductionmentioning
confidence: 99%